The Impacts of Skiing and Related Winter Recreational Activities on Mountain Environments - Rixen, Christian; Rolando, Antonio (Bentham Science Publishers, 2013)
This e-book reviews environmental impacts of ski tourism in mountain environments. Specifically, the book addresses skiing impacts on soils, vegetation, vertebrate and invertebrate animals living in such habitats. Additional chapters also explain the methods for the restoration of disturbed sites at high altitude and snow cover in a changing climate. The e-book is therefore a compilation on the latest knowledge on environmental impacts of skiing and is intended to be a standard reference for ecologists, students and universities, business professionals (ski-resort managers), regional governmental organizations, conservation agencies and non-governmental organizations (NGOs).